Five things to know about Trump's FY19 budget request. Issue 2 (16th April 2018) - Pierson, Steve
Abstract : BySteve Pierson, director of science policy, American Statistical Association (ASA) Abstract : By Steve Pierson, director of science policy, American Statistical Association (ASA).